Bairro, futebol e territorialidades: Campinas e o Atlético clube goianiense - Prado, Cristina Maria Costa (2018)
Campinas was a village that belonged to the city of Goiânia and it was chosen to support the construction of the new city. The village was incoorporatted to the city becoming a disctrict. This fact brought a variety of modifications to the urban landscape and to the cultural aspects. In this way some tradittions were lost and the way of life have given space to to the news ones. In this role of losses some territorialities stand out and are fundamentals as support of memory of the district and apparatus for the Campinas identity. One of those is the soccer team “Atletico Clube Goianiense”, which arised in the middle of Campinas in 1937 but doesn’t belongs to the adiministrative limito f the district. It was a fundamental element as way of manifestation the rivality between Goiânia and Campinas in the capital development period. Contributing, then, to the mainnantance of the traditions and the simbolic elements of the Society of Campinas. The soccer team had lived glorious moments and decadence with the unconditional support of its crowd, specially when they saw themseves in the eminence of loose its greater patrimony the Antonio Accioly Stadium. Hence, this study had the goal of understand who is the Atletic fan and how his territoriality performs the function of memory transmitter and part of the identity construction of the district. In this way, sought for authors that have explored the territory, terriotarialities and reterritorialities issues. As well as it was searched for author that have discussed identity andmemory aspects about rites and symbols and another pertinent issues. The etonographic exercise, the taxonomic classifications and oral sources were chosen as instruments for this discussion.